Phenylketonuria and juvenile idiopathic arthritis: a case report - Ting Ting Zhu; Jin Wu; Li Yuan Wang; Xiao Mei Sun (BMC, 2021)
Abstract Background Phenylketonuria (PKU) is a genetic metabolic disorder in which patients have no ability to convert phenylalanine to tyrosine. Several autoimmune diseases have been reported to combine with PKU, co-existent of PKU and Juvenile Idiopathic Arthritis (JIA) has not been presented. Case presentation The girl was diagnosed with PKU at the age of 1 month confirmed by molecular data. At the age of 3.5 years, she presented with pain and swelling of her right ankle, right knee, and right hip joint. After a serial of examinations, she was diagnosed with JIA and treated with a nonsteroidal anti-inflammatory drug. Conclusions We report a rare case of a 4-year-old girl with PKU and JIA, which supports a possible interaction between PKU and JIA. Long-term metabolic disturbance may increase the susceptibility to JIA. Further chronic inflammation could alter the metabolism of tryptophan and tyrosine to increase blood Phe concentration. In addition, corticosteroid and methotrexate therapy for JIA may increase blood Phe concentration.